2021
DOI: 10.1371/journal.pone.0259539
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling in bovine serum according to the stage of Mycobacterium avium subsp. paratuberculosis infection

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of Johne’s disease (JD), and it causes diarrhea and weakness in cattle. During a long subclinical stage, infected animals without clinical signs shed pathogens through feces. For this reason, the diagnosis of JD during the subclinical stage is very important. Circulating miRNAs are attracting attention as useful biomarkers in various veterinary diseases because of their expression changes depending on the state of the disease. Based on cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Similarly, Shaughnessy et al did not detect differentially expressed miRNAs at either the early 6 months or late (43, 46, and 49 months) intervals across seropositive and seronegative animals 34 . Using naturally infected cattle previous studies compared the miRNA profiles of cattle positive and negative for MAP antibodies by ELISA 32 or compared miRNA profiles according to the stage of MAP infection defined by fecal shedding, ELISA, and clinical signs 53 . In cattle, however, signs of infection such as the appearance of focal lesions in gut tissues can be detected before fecal shedding and ELISA, and therefore, examining the transcriptome of animals according to the histopathological lesions facilitates the identification of animals in the subclinical stage of the infection when the amount of MAP and antibodies can be undetected with current pre-mortem diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shaughnessy et al did not detect differentially expressed miRNAs at either the early 6 months or late (43, 46, and 49 months) intervals across seropositive and seronegative animals 34 . Using naturally infected cattle previous studies compared the miRNA profiles of cattle positive and negative for MAP antibodies by ELISA 32 or compared miRNA profiles according to the stage of MAP infection defined by fecal shedding, ELISA, and clinical signs 53 . In cattle, however, signs of infection such as the appearance of focal lesions in gut tissues can be detected before fecal shedding and ELISA, and therefore, examining the transcriptome of animals according to the histopathological lesions facilitates the identification of animals in the subclinical stage of the infection when the amount of MAP and antibodies can be undetected with current pre-mortem diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
“…miR-27a-5p acts as a negative regulator of adipocyte differentiation and lipid metabolism and a positive regulator of cell proliferation [ 57 ]. miR-2887 is involved in the regulation of immune and inflammatory responses [ 58 ]. Also, miR-11987 and miR-11972 have been shown to be involved in the autophagic process by negatively regulating their target genes, RAC3 and CLN7 [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-2887 is involved in the regulation of immune and inflammatory responses [ 58 ]. Also, miR-11987 and miR-11972 have been shown to be involved in the autophagic process by negatively regulating their target genes, RAC3 and CLN7 [ 58 , 59 ]. RAC3 is a negative regulator of autophagy; therefore, its downregulation by miR-11972 could promote autophagy in DFD beef.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, miR-363 was upregulated during Mycobacterium avium subsp. paratuberculosis infection [ 54 ]. We found that this miRNA was elevated in spleen and lymph node, consistent with a role in inflammation.…”
Section: Discussionmentioning
confidence: 99%